Synthesis of the natural product descurainolide and cyclic peptides from lignin-derived aromatics. Issue 2 (15th December 2017) - Ojo, O. Stephen; Nardone, Brunello; Musolino, Stefania F.; Neal, Andrew R.; Wilson, Liam; Lebl, Tomas; Slawin, Alexandra M. Z.; Cordes, David B.; Taylor, James E.; Naismith, James H.; Smith, Andrew D.; Westwood, Nicholas J.
Abstract : Alternative sources of potential feedstock chemicals are of increasing importance as the availability of oil decreases. Abstract : Alternative sources of potential feedstock chemicals are of increasing importance as the availability of oil decreases. The biopolymer lignin is viewed as a source of useful mono-aromatic compounds as exemplified by the industrial scale production of vanillin from this biomass. Alternative lignin-derived aromatics are available in pure form but to date examples of the use of these types of compounds are rare. Here we address this issue by reporting the conversion of an aromatic keto-alcohol to the anti - and syn -isomers of Descurainolide A. The key step involves a rhodium-catalyzed allylic substitution reaction. Enantio-enriched allylic alcohols were generated via an isothiourea-catalyzed kinetic resolution enabling access to both the (2 R, 3 R ) and (2 S, 3 S ) enantiomers of anti -Descurainolide A. In addition we show that the lignin-derived keto-alcohols can be converted into unnatural amino acid derivatives of tyrosine. Finally, these amino acids were incorporated into cyclic peptide scaffolds through the use of both chemical and an enzyme-mediated macrocylisation.